Frailty links the heterogeneity of tinnitus disorder and response to interventions in older patients - Ruan, Jian; Zhang, Min; Han, Zhao; Chen, Jie; Ruan, Qingwei; Bao, Zhijun (Frontiers in Neurology, 2025)
In addition to having a sensory component, tinnitus disorder might also be involved in tinnitus-related distress, cognitive dysfunction, and/or autonomic arousal, resulting in different behavioral changes and functional disabilities. The response to interventions has been shown to be heterogeneous in patients with tinnitus disorder. The underlying neural mechanisms of the heterogeneity of tinnitus disorder and their response to interventions remain elusive. Frailty and tinnitus share similar risk factors, including genetics; personality; early experience, aging and psychosocial stress; aging-related chronic systemic inflammation; vascular damage; neurodegenerative pathology; and functional decline in physical, cognitive, and psychosocial dimensions. The mechanisms by which frailty is linked to tinnitus disorder involve dysfunction of the HAP axis, cognitive and emotional processing, autonomic reactivity, and immune and metabolic regulation. Moreover, tinnitus, as a stressor, results in increased allostatic load, maladaptation, and adverse outcomes in individuals with frailty. The maladaptation induced by frailty contributes to the heterogeneity of tinnitus disorder, and the response to intervention is the synchronization of intrinsic brain networks characterized by increased integration and decreased segregation. Frailty may be associated with tinnitus chronification and relapse after effective intervention. We propose a model hypothesis to explain the bidirectional relationship between frailty and tinnitus disorder. In this model, the dysfunction of dynamic executive functioning might be the common pathway of tinnitus disorder and frailty. Investigating the efficacy of interventions for older people with frailty and tinnitus disorder will provide evidence about their benefits and disadvantages. Further exploration of vulnerability-related cortical and subcortical biomarkers of frailty and tinnitus disorder could provide guidance for the understanding and personalized prevention of tinnitus disorder.